2005
DOI: 10.1086/431990
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Toll-Like Receptor 2 Polymorphisms in Severe Infections

Abstract: Toll-like receptor 2 (TLR2) is a member of the TLR family, which plays a central role in the innate immune response to a wide variety of microorganisms. Animal studies have shown that TLR2-knockout mice are more susceptible to septicemia due to Staphylococcus aureus and Listeria monocytogenes, meningitis due to Streptococcus pneumoniae, and infection with Mycobacterium tuberculosis, suggesting that functional TLR2 polymorphisms may impair host response to a certain spectrum of microbial pathogens. In humans, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
2
11

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 48 publications
1
121
2
11
Order By: Relevance
“…267 Furthermore, the coupling of these pattern recognition receptors to downstream adaptor molecules also appear to be distinct as shown by disparities in clinical outcomes in humans with IRAK-4 deficiency versus the susceptibility to pathogens in knockout mice. 268 It is also important to note that significant polymorphisms in TLRs exist which have been shown to be associated with altered innate immune responses [269][270][271] and, by extension, would therefore also be expected to have pronounced effects on the shaping of adaptive immune responses. In practical terms, these considerations emphasize the necessity of examining human innate immune responses (preferably using primary cells ex vivo, with a sufficiently large sample size to account for heterogeneities in responses), even in preliminary studies aimed at screening for immunopotentiatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…267 Furthermore, the coupling of these pattern recognition receptors to downstream adaptor molecules also appear to be distinct as shown by disparities in clinical outcomes in humans with IRAK-4 deficiency versus the susceptibility to pathogens in knockout mice. 268 It is also important to note that significant polymorphisms in TLRs exist which have been shown to be associated with altered innate immune responses [269][270][271] and, by extension, would therefore also be expected to have pronounced effects on the shaping of adaptive immune responses. In practical terms, these considerations emphasize the necessity of examining human innate immune responses (preferably using primary cells ex vivo, with a sufficiently large sample size to account for heterogeneities in responses), even in preliminary studies aimed at screening for immunopotentiatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 reacts with PAMPs found in both Gram-positive and Gram-negative bacteria, and TLR2-deficient mice are much more susceptible to infections than their wild-type counterparts (16). TLR11, the most recently identified member of TLR family, has been found to be capable of preventing urinary tract infections (10,17).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…To date, several studies have demonstrated that some naturally occurring TLR variants enhance the risk of severe infections in humans, mice, and most recently, domestic cattle (23)(24)(25)(26). In addition to the emerging molecular and population-based casecontrol data, bovine health-related quantitative trait loci (QTL) have been localized to genomic regions either proximal to or directly overlapping one or more TLR loci, and at least two healthrelated QTL are proximal to PGLYRP1 (25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%